2013
DOI: 10.1007/s00339-013-7935-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quantum well inhomogeneities on absorption, spontaneous emission, photoluminescence decay time, and lasing in polar InGaN quantum wells emitting in the blue-green spectral region

Abstract: It is shown that in polar InGaN QWs emitting in the blue-green spectral region a Stokes shift between spontaneous emission (SE) and optical transition observed in contactless electroreflectance (CER) spectrum (absorptionlike technique) can be observed even at room temperature, despite the fact that the SE is not associated with localized states. Time resolved photoluminescence measurements clearly confirm that the SE is strongly localized at low temperatures whereas at room temperature the carrier localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The PL measurements were complemented by electromodulation spectroscopy together with calculations within the random QW model. 24,25,28,29) Our results show that the QW built-in electric field enhances the PL broadening related to the previously invoked mechanisms involving local inhomogeneity. Additionally, we have shown that the exciton-phonon coupling can be controlled using an external bias.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…The PL measurements were complemented by electromodulation spectroscopy together with calculations within the random QW model. 24,25,28,29) Our results show that the QW built-in electric field enhances the PL broadening related to the previously invoked mechanisms involving local inhomogeneity. Additionally, we have shown that the exciton-phonon coupling can be controlled using an external bias.…”
supporting
confidence: 54%
“…22,23) It has been shown theoretically that the electric field significantly impacts the transition broadening in InGaN=GaN QW. [24][25][26] However, there is no experimental work that quantifies how strong this effect is in the InGaN=GaN QW system. Some indication of the PL broadening enhancement due to an increased electric field has been reported for polar quantum wells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On one side, this width cannot be too small (d<2 nm) because of the weak quantum confinement, and on the other side this width cannot be too large (d>4 nm) because of small electron-hole overlap integral. Additionally it is worth noting that alloy inhomogeneities (i.e., fluctuations of QW width and content) manifest themselves much stronger in the optical properties of narrow QWs [58,60] and therefore narrow QWs (d<2 nm) will exhibit a rather broad luminescence which can be an unwanted feature of UV LEDs. Taking into account the above results and arguments we concluded that the optimal QW width for the active region in UV LEDs is in the range of 2-4 nm.…”
Section: Resultsmentioning
confidence: 99%
“…This suppression of the spectral dependence of the PL decay time with increasing temperature has been reported by several groups. 49,[53][54][55][56] In these works, 49,53-55 the measured decay curves at room temperature were single exponential and independent of detection energy which was ascribed to the effects of non-radiative recombination. However, the samples discussed here are quite efficient at 300 K with IQEs of 25(62)% and 36(62)% for sample A and sample B, respectively.…”
Section: -4mentioning
confidence: 90%